2019
DOI: 10.1002/evl3.101
|View full text |Cite
|
Sign up to set email alerts
|

Selection for longer lived sperm within ejaculate reduces reproductive ageing in offspring

Abstract: Males produce numerous sperm in a single ejaculate that greatly outnumber their potential egg targets. Recent studies found that phenotypic and genotypic variation among sperm in a single ejaculate of a male affects the fitness and performance of the resulting offspring. Specifically, within‐ejaculate sperm selection for sperm longevity increased the performance of the resulting offspring in several key life‐history traits in early life. Because increased early‐life reproductive performance often correlates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…This inefficiency may be particularly pronounced when the storage organs are largely full, as would be the case so soon after mating (5 h). Despite appearing wasteful, profligacy in sperm release may be adaptive if it encourages further competition between sperm of varying quality, with consequences for offspring fitness (5759). However, profligacy also serves to more rapidly deplete the sperm storage organs, giving an increased advantage to the second mating male.…”
Section: Resultsmentioning
confidence: 99%
“…This inefficiency may be particularly pronounced when the storage organs are largely full, as would be the case so soon after mating (5 h). Despite appearing wasteful, profligacy in sperm release may be adaptive if it encourages further competition between sperm of varying quality, with consequences for offspring fitness (5759). However, profligacy also serves to more rapidly deplete the sperm storage organs, giving an increased advantage to the second mating male.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in the zebrafish showed that sperm traits vary with the intensity of male-male competition and male social status and affect the survival and performance of the resulting offspring (Zajitschek et al 2014;Zajitschek et al 2017), possibly due to the higher mutational load in sperm of stressed males (Silva et al 2019). In addition, longer-lived sperm selected within ejaculates sire embryos with higher survival and adult fitness in zebrafish (Alavioon et al 2019) (Darszon et al 2004) and in several species of externally fertilizing fish (Yanagimachi et al 1992). Similarly, in the mussel, M. galloprovincialis, differential attraction of sperm from the most compatible male is attributable to egg-derived chemical factors (Evans et al 2012;Lymbery et al 2017;Oliver and Evans 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative (although non-mutually exclusive) explanation to nongenetic changes could be that environmental stress, such as high temperature, imposes selection among genetically different haploid sperm within an ejaculate, such that certain sperm haplotypes are more successful and transmit genes that are beneficial for normal offspring development [29]. For example, recent elegant experiments in zebrafish have shown that phenotypic variation within an ejaculate can reflect haploid genetic variation, and selection among phenotypes can affect offspring traits [30,31]. Given previous evidence that heat stress alters sperm RNA content in M. galloprovincialis [10] while the proportion of motile sperm in ejaculates remains constant, we suggest that epigenetic changes are the more likely mechanism underlying paternal effects reported here.…”
Section: Discussionmentioning
confidence: 99%